A Preliminary Sociophonetic Study on Schwa Epenthesis in Dublin English - Christophe Coupé (Anglophonia)
This exploratory study focuses on schwa epenthesis from a quantitative point of view and is based on a corpus of wordlists read by 65 Dubliners recorded in 2021. Schwa epenthesis is a well-known feature of Irish English found in the Irish substratum where the phonotactic structure avoids consonant clusters. Schwa is therefore added in order to break up the cluster. This feature of Irish English has also been observed in Dublin English, but to a lesser extent. Schwa epenthesis will first be defined in the context of Irish English and Dublin English. Then, the method for the identification of schwa epenthesis will be discussed; the results will then be presented and discussed. Schwa epenthesis was analysed in three word-final clusters, /rl/, /rm/ and /rn/, and /rl/ proved to be the most productive. This study analysed schwa epenthesis according to four variables: the speakers’ age, gender, place of origin, and mobility. Out of the 520 environments analysed, only 39 were realised with schwa epenthesis and the /rl/ cluster proved to be the most productive. Only gender showed a statistically significant influence on the frequency of occurrence of schwa epenthesis: men resorted to it more than women in our corpus.